Automatic Processing of Nasal Pressure Recordings to Derive Continuous Side-Selective Nasal Airflow and Conductance - Urner, Lorenz M.; Kohler, Malcolm; Bloch, Konrad E. (Frontiers in Physiology, 2019)
The continuous monitoring of nasal airflow and conductance reveals crucial insight into the variable nature of nasal resistance, nasal cycle, breathing pattern, and ventilation. Unobtrusive tracking of side-selective nasal pressure by a specially designed catheter system at the entrance of each nasal passage can serve as a means for monitoring side-selective nasal airflow over several hours if a suitable linearization procedure and calibration are applied. Side-selective nasal conductance is obtained as calculated ratio of the derived nasal airflow and simultaneously recorded epipharyngeal pressure. Manual analysis of nasal flow and epipharyngeal pressure recordings and computation of instantaneous conductance over several hours is extremely tedious, time consuming and therefore not practicable. To address this point, we describe the signal processing principles and validation of a computer program, which performs automatic calibration using an 8-parameter logistic model and processing of side-selective nasal pressure recordings into airflow and, in combination with epipharyngeal pressure, conductance. Pressure recordings may be subdivided into user-defined consecutive time-segments (e.g. 2 min intervals) and processed by 1) offset correction, 2) low-pass filtering, 3) cross-correlation, 4) cutting of signals into individual breaths, 5) normalization, 6) ensemble averaging to obtain a mean pressure signal for each nasal side, 7) derivation of airflow, conductance and further variables. Comparison of four algorithms for the calculation of nasal conductance revealed that the derivative of the airflow-pressure curve according to the mean value theorem gave good agreement with the gold standard, independent flow-meter-derived conductance, according to a Bland-Altman analysis. In combination with the nasal catheter system, our nasal signal processing software represents a valuable tool for the convenient evaluation of nasal physiology and of disturbances of nasal ventilation over time.